2018
DOI: 10.3389/fmicb.2017.02660
|View full text |Cite
|
Sign up to set email alerts
|

Applications for Bacteriophage Therapy during Pregnancy and the Perinatal Period

Abstract: Pregnant women and their unborn children are a population that is particularly vulnerable to bacterial infection. Physiological changes that occur during pregnancy affect the way women respond to such infections and the options that clinicians have for treatment. Antibiotics are still considered the best option for active infections and a suitable prophylaxis for prevention of potential infections, such as vaginal/rectal Streptococcus agalactiae colonization prior to birth. The effect of such antibiotic use on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 150 publications
(183 reference statements)
0
35
0
1
Order By: Relevance
“…They concluded that Ն70% vaccine efficacy in addition to IAP for unvaccinated women would prevent more disease than current strategies, with a similar economic burden (145). Epidemiological data about GBS are invaluable not only for vaccine development and success but also for other future targeted therapeutic agents, such as bacteriophage therapy (146).…”
Section: From Targets To Treatmentmentioning
confidence: 99%
“…They concluded that Ն70% vaccine efficacy in addition to IAP for unvaccinated women would prevent more disease than current strategies, with a similar economic burden (145). Epidemiological data about GBS are invaluable not only for vaccine development and success but also for other future targeted therapeutic agents, such as bacteriophage therapy (146).…”
Section: From Targets To Treatmentmentioning
confidence: 99%
“…If lytic phages specific for these bacteria were to be identified, these bacteria could be eliminated from the genital tract without affecting the surrounding vaginal microbiota. However, phage therapy has yet to be explored in pregnancy …”
Section: Alternative Avenues For Treatmentmentioning
confidence: 99%
“…The lytic cycle implies bacterial death, which generates virion output. For this, they take advantage of the replication system of the host cell, and when their proteins and viral components are formed, they induce cell lysis [ 18 , 19 ]. In contrast, lysogenic cycles are based in the integration of the genetic material of the phage into the genome of the host cell.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, lysogenic cycles are based in the integration of the genetic material of the phage into the genome of the host cell. At the end of the replication cycle, no new virions are obtained, but bacterial cells with phage genetic material are created, as temperate phages [ 18 ]. Due to the variability between phages, it is important to determine which are the most appropriate bacteriophages for each potential application [ 20 ].…”
Section: Introductionmentioning
confidence: 99%